Pengaruh Brand Ambassador “Tasya Farasya” Dan Brand Trust Terhadap Minat Beli Avoskin Di Aplikasi Instagram Pada Mahasiswa - Nurmarisma, Chalida; Savitri, Citra; Fadilla, Syifa Pramudita (Universitas Muhammadiyah Metro, 2023)
The cosmetics industry is expanding extremely quickly, and in Karawang Regency, fans andconsumers of cosmetics bearing the Avoskin brand have started to rise sharply. The goal ofthis study was to evaluate and quantify the impact of Tasya Farasya as a brand ambassadorand consumer interest in purchasing cosmetics bearing the Avoskin brand. The research isquantitative in nature. The quantitative approach method is the one used. The authors usedGoogle Forms to disseminate online surveys as part of the data gathering procedure. 96samples were utilized in the analysis. The analysis employed descriptive analysis withmultiple regression using SPSS version 21. The sampling approach used non-probabilitysampling technique. Brand ambassadors have a good and substantial impact on purchaseintention, according to the study's findings. Purchase intention is positively and significantlyimpacted by brand trust. Purchase intentions are simultaneously influenced by brand trustand brand advocates.